EFISIENSI BIMBINGAN PRANIKAH OLEH PENYULUH AGAMA ISLAM DALAM UPAYA MEMBENTUK KELUARGA SAKINAH DI KUA SRENGAT - Rokhanianto, Mochamad; Arifin, Mochammad (SINDA: Comprehensive Journal of Islamic Social Studies, 2023)
Marriage is formed through a sacred bond between a man and a woman, said to be sacred because it is regulated by religion and then confirmed by state laws , customs and society. Pre-marital guidance itself is something that must be done and prepared in order to obtain provisions to live a new life. The importance of premarital counseling is due to several aspects, including problems of individual differences, economic problems, problems of individual development and problems of socio-cultural background. This is what encourages researchers to conduct research. Islamic Religion Counselors as well as guidance partners of the Directorate General of Islamic Community Guidance, and as the spearhead in carrying out the task of guiding Muslims in achieving a quality and prosperous life both physically and spiritually. This study aims to find out the role of the Islamic Religious Counselor at the KUA in Srengat District in providing religious guidance or counseling to the community in an effort to form a sakinah family. What is the method used by Islamic Religious Counselors in changing the paradigm of society in understanding sakinah families and how is the process of premarital guidance taking place at KUA Srengat District. This study uses an approach qualitative. The data collection method is through observation, interviews and documentation. The research objects are: Islamic Religious Counselors at the KUA Srengat, while the subjects of this research are the people in the Srengat area (youths who have married and who will carry out the marriage). The number of informants who were the target of this research data source were two prospective brides, two newlyweds (married) and one Islamic religious instructor. In this study, the researchers proved that the role of the Islamic Religious Counselor in providing premarital guidance to the community was quite efficient, because the function of the Islamic Religious Counselor at the Srengat District Office of Religious Affairs was to convey information to the public and give advice or so-called guidance, function as a consultant and function as an advocate. . The method used by the Islamic Religion Counselor at KUA Srengat to change the community's paradigm in understanding the meaning of a sakinah family is by providing an explanation of the position of the prospective husband and wife, the rights and obligations of the husband and wife, the joint rights of the husband and wife, and the joint obligations of the husband and wife. The process of pre-marital guidance carried out by Islamic Religion Counselors at the KUA in Srengat District uses two methods, namely directly and indirectly. Straight to the point Every couple who registers a marriage at the KUA is required to attend pre-marital counseling. When following the guidance, the bride and groom will be asked questions related to the sakinah family. Indirect premarital guidance is done online (via a temporary wasap group formed after registering until one month after the wedding), via Facebook and YouTube. Keywords: Efficiency of Premarital Guidance, Efforts to form Sakinah Family